2020
DOI: 10.1007/s00429-020-02032-7
|View full text |Cite
|
Sign up to set email alerts
|

A positive influence of basal ganglia iron concentration on implicit sequence learning

Abstract: Iron homeostasis is important for maintaining normal physiological brain functioning. In two independent samples, we investigate the link between iron concentration in the basal ganglia (BG) and implicit sequence learning (ISL). In Study 1, we used quantitative susceptibility mapping and task-related fMRI to examine associations among regional iron concentration measurements, brain activation, and ISL in younger and older adults. In Study 2, we examined the link between brain iron and ISL using a metric derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 103 publications
7
6
0
Order By: Relevance
“…These results coincide with a growing body of functional [9,11,44,[50][51][52][53], structural [10], and genotypic [28] evidence showing that basal ganglia (particularly caudate) relates to both early and late stages of learning. Moreover, our finding that globus pallidus, not just caudate, microstructure contributes to IAL performance is consistent with emerging work [11,53], potentially signifying that later learning is affected by differences in the presence of iron or other microstructural alterations like dendritic arborization that may have a larger impact on extracellular sources of diffusion captured by the hindered diffusion metric. In contrast, early learning may be impacted by differences in neurite density or other intracellular neurobiological substrates captured by the restricted diffusion metric in caudate.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…These results coincide with a growing body of functional [9,11,44,[50][51][52][53], structural [10], and genotypic [28] evidence showing that basal ganglia (particularly caudate) relates to both early and late stages of learning. Moreover, our finding that globus pallidus, not just caudate, microstructure contributes to IAL performance is consistent with emerging work [11,53], potentially signifying that later learning is affected by differences in the presence of iron or other microstructural alterations like dendritic arborization that may have a larger impact on extracellular sources of diffusion captured by the hindered diffusion metric. In contrast, early learning may be impacted by differences in neurite density or other intracellular neurobiological substrates captured by the restricted diffusion metric in caudate.…”
Section: Discussionsupporting
confidence: 79%
“…The present study examined age group differences in IAL as a function of learning stage, age group differences in basal ganglia and hippocampal gray matter microstructure, relationships between IAL and gray matter microstructure across age groups, and whether these IALmicrostructure relationships were moderated by age. We extended earlier work by assessing microstructure of subcortical gray matter and by controlling for iron content, which is known to increase with age [24,[39][40][41][42], affect diffusion [23,25], and relate to learning [11]. In line with our predictions, older adults exhibited deficits in IAL and differences in diffusion across all three metrics for the basal ganglia (caudate, putamen) and hippocampus compared to young adults.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This pattern of results is consistent with our recent diffusion imaging work, in which we found that microstructural integrity of globus pallidum (and caudate) gray matter related to better late IAL performance in younger and older participants from the current study (Franco et al, 2020), thereby providing converging evidence between structural and functional markers of IAL. We previously argued, like others (Persson et al, 2020), that the neural substrates of IAL may be influenced by the presence of iron, which can attenuate the MR signal at acquisition (Haacke et al, 2005) and across basal ganglia regions that differentially accumulate iron across the lifespan (Hallgren and Sourander, 1958). For example, we may be more sensitive to age group differences in neural markers of IAL in basal ganglia regions that gradually accumulate moderate amounts of iron throughout the lifespan (caudate, putamen) compared to regions that accumulate large amounts of iron by early adulthood (globus pallidum).…”
Section: Discussionsupporting
confidence: 73%